CELIAC DISEASE AMONG GASTROINTESTINAL PATIENTS IN YEMEN: ITS PREVALENCE, SYMPTOMS AND ACCOMPANYING SIGNS, AND ITS ASSOCIATION WITH AGE AND GENDER - Al-dossary, Omar Ahmed Ismael; Ahmed, Redhwan A.; Al-Moyed, Khaled Abdulkareem A; Al-Ankoshy, Azhar Azher Mohammed; Al-Najhi, Mohammed Mohammed Ali; Al-Shamahy, Hassan Abdulwahab (Universal Journal of Pharmaceutical Research, 2021)
Background and objectives: Celiac disease is a long-standing autoimmune illness that principally affects the small intestine. Typical symptoms comprise digestive problems such as chronic diarrhea, flatulence, malabsorption, loss of appetite, and failure of children to grow normally. The prevalence of celiac disease has not been established in Yemen, either in the general population or in symptomatic patients. Therefore, the current study aimed to assess the prevalence of disease in symptomatic patients and to investigate associated symptoms and signs; and whether prevalence of CD varies greatly between different ages and genders in a hospital in Sana'a. Methods: A cross sectional study based on the results of serological markers; IgA anti-tissue glutaminase and small bowel biopsies of 600 patients with gastrointestinal symptoms who were all patients who attended in the research period. Data were collected from hospital records during the period from March 2014 to December 2018. 600 suspected patients (245 males and 355 females) were subjects and the mean age of ±SD patients was 30.6±14.5 years (range 2-92 years). Results: The prevalence of CD among patients with gastrointestinal symptoms was 9.2%. There was a significant association between CD with females (rate being 11.3% , OR=1.9, p=0.03), and 2-19 years age group (21.4% , OR=4.3, p<0.001), Considering the clinical signs and symptoms there was a significant association between celiac disease and chronic diarrhea (OR=18.4), steatorrhea ( OR=9.6), foul odor (OR=8.3), weight loss (OR=5.7), anemia (OR=10.2), abdominal distension (OR=3.1), mouth ulcers (OR=7.2), abdominal bleeding (OR=13.5), diabetes mellitus I (OR=18), and hypothyroidism (OR=79.3). Conclusion: A high rate of CD was identified among gastrointestinal symptoms patients arriving at the general hospital in Sana’a, Yemen, and this demonstrates the importance of general practitioners in identifying patients with CD, especially in the absence of a medical facility for CD, and this was facilitated through the serological markers test. Peer Review History: Received: 1 August 2021; Revised: 5 September; Accepted: 8 October; Available online: 15 November 2021 Academic Editor: Ahmad Najib , Universitas Muslim Indonesia, Indonesia, ahmad.najib@umi.ac.id Reviewers: Dr. Gulam Mohammed Husain, National Research Institute of Unani Medicine for Skin Disorders, Hyderabad, India, gmhusain@gmail.com Dr. Vanina Doris Edo’o, University of Yaounde I, Yaounde, Cameroun, vanina_edoo@yahoo.com